OCCURRENCE OF THE SACRED CHANK, XANCUS PYRUM (LINNAEUS) OFF PORTO NOVO - Pillai, P K Mahadevan; Devadoss, P (Indian Journal of Fisheries, 2011)
The sacred chank, Xancus pyrum (Linnaeus) is an important gastropod exploited commercially in a few maritime states in India; the major portion is from Gulf of Mannar and Palk Bay. Nayar and Mahadevan (1973) gave the details of chank resources of India suggesting possibilities of exploiting them from unfished waters